Redox‐Active Organic Electrode Materials for Supercapacitors - Ding, Wei; Xiao, Luyi; Lv, Li‐Ping; Wang, Yong (Batteries & supercaps, 2023)
Due to their prominent power density, supercapacitors carve out a niche among all the energy storage systems. However, it is also well known that the energy density of supercapacitors takes no advantage over lithium‐ion batteries, the current star energy storage device. Therefore, substantial efforts have been paid to improving the energy density of supercapacitors not at the expense of its power density. To develop electrode with high capacitance is a direct and efficient way to increase the energy storage capability of supercapacitors. Organics whose molecular structure can be diversely designed to achieve high pseudocapacitance arising from redox‐active units in their backbone are good candidates as electrode materials for supercapacitors. Herein, this review summarizes recent progress of redox‐active organic electrode materials for supercapacitors and their pseudocapacitive energy storge mechanisms based on different organic functional groups. From the aspects of their preparation approaches, molecular design and the resultant electrochemical performances, the focus is to probe the relationship between the energy storage mechanisms and the molecular structure of redox‐active units and provide some insights for the further development of organic supercapacitor electrodes.